Perlindungan Nasabah pada Lembaga Keuangan Syariah - Nining Aja Liza Wahyuni (Jurnal Hukum Ekonomi Islam, 2018)
Sharia economics is defined as an economic system based on Islamic principles (sharia). Its scope is all existing economic sectors, both financial and real sectors. The sharia economic system must also provide equitable and sustainable benefits (maslahah) for every element in the economy. Protection of customer rights at the time of the transaction is a legal protection obtained by the customer when making a transaction or when entering into a contract agreement both deposits and credit. However, most protections at the time of this transaction are often ignored by a bank itself. Regarding the implementation of financial institutions in Indonesia, every customer has the right to legal certainty in guaranteeing the protection of his rights. 'Spiritual rights' is a new concept, but basically it is a crystallization of several concepts that already exist in society. The introduction of such new terms can be interpreted as an effort to increase awareness about an important thing that exists around consumers. Keywords: Islamic Financial Institutions, Spiritual Rights. Abstract Ekonomi syariah ini diartikan sebagai sistem ekonomi yang berlandaskan prinsip Islam (syariah). Cakupannya adalah seluruh sektor perekonomian yang ada, baik keuangan maupun sektor riil. Sistem ekonomi syariah juga harus memberikan manfaat (maslahah) yang merata dan berkelanjutan bagi setiap elemen dalam perekonomian. Perlindungan hak-hak nasabah pada saat transaksi merupakan perlindungan hukum yang diperoleh nasabah saat melakukan transaksi atau saat melakukan perjanjian kontrak baik simpanan maupun kredit. Akan tetapi kebanyakan perlindungan pada saat transaksi ini sering terabaikan oleh suatu bank itu sendiri. Terkait dengan dalam penyelenggaraan lembaga keuangan di Indonesia, setiap nasabah berhak atas kepastian hukum dalam menjamin perlindungan akan hak-haknya. ’hak spiritual’ adalah konsep baru, namun pada dasarnya merupakan kristalisasi dari beberapa konsep yang telah ada dalam masyarakat. Pengenalan dengan istilah baru demikian dapat dimaknai sebagai upaya peningkatan kesadaran tentang suatu hal penting yang ada disekitar konsumen. Keywords: Lembaga Keuangan Syariah, Hak Spiritual.